ENTITAS TANPA AKUNTABILITAS PUBLIK (ETAP) DI PERSIMPANGAN UNDANG – UNDANG PERKOPERASIAN (Telaah kritis keterterapan ETAP dalam Pelaporan Keuangan Koperasi) - Bayangkara, IBK (Universitas 17 Agustus 1945 Surabaya, 2019)
ABSTRACT This study aims to examine the adequacy of SAK ETAP as a cooperative financial reporting standard in Indonesia. With a literature study approach, the authors examine the ability of SAK ETAP in meeting the provisions of Law No. 25 of 1992 concerning Cooperatives, as well as comparing them to PSAK 27 concerning Cooperatives that have been revoked. This research found that to date SAK ETAP has not been able to meet the provisions of Law No. 25 of 1992 in cooperative financial reporting because it does not explicitly present members' economic promotion reports, which is very important information that must be presented to users of cooperative financial statements. This is a new finding because research on the adequacy of SAK ETAP as a cooperative financial reporting standard has never been done before. The results of this study have implications for the obligations of the IAI Standards Board to immediately adjust SAK ETAP to be able to meet the needs of users of cooperative financial reports on relevant information as a basis for making decisions. Keywords: ETAP, Cooperatives, Financial Statements, Act 25 1992, Promotion of Members' Economy